Effect of Arm Muscles and Long Arm Power Exercises on the Results of Accuracy in Forehand Smash Blows in Table Tennis Games at Silaberanti Club, Palembang (Study Program Education and Sports, Postgraduate Universitas Negeri Semarang, 2019)
This study aims to analyze the method of arm muscle power training with the results of the accuracy of the forehand smash to Silaberanti athletes, Palembang, to find out the difference between athletes who have long arms and short arms with the results of the forehand smash in table tennis at Silaberanti club, Palembang, to analyze the interaction between the training method of arm muscle power and arm length with the results of the accuracy of the forehand smash in table tennis athletes at Silaberanti club, Palembang. This study used a quasi-experimental method using a 2x2 factorial design. Data analysis techniques used variant Analysis (ANOVA) at a significant level of Î± = 0.05. The subject of this research was the table tennis athlete at Silaberanti club, Palembang, South Sumatra. The results of this study show: there is the influence of high swing dumbbell training method and push-ups on the results of the accuracy of the forehand smash in table tennis at Silaberanti club, Palembang, there is no difference in influence between athletes who have a short arm and long arm category on the results of the forehand smash in table tennis at Silaberanti club, Palembang, there is an interaction effect between the method of high swing dumbbell training and push-up with arm length on the results of the accuracy of the forehand smash in table tennis at Silaberanti club, Palembang. Suggestions for sports coaches can be to use the dumbbell hight swing training method and push-ups for arm muscle power by combining strength at speed, and for similar studies can develop further research with broader coverage.